Investigating the Relationship among Organizational Culture, Job Motivation, Organizational Citizenship Behaviour, and Job Performance: Indonesian Public Sector Context - Siswanto, Ari; Nadia, Fiona Niska Dinda (RSF Conference Series: Business, Management and Social Sciences, 2024)
The inadequate performance of Indonesia’s public sector is demonstrated by the decline in ranking on the Global Competitiveness Index from 2017 to 2019 and the lack of research on OCB in the public sector, considering that most studies focus on the private sector. The objective of this study is to explore the correlation between organizational culture, work motivation, work performance, and organizational citizenship behavior (OCB) within Indonesia’s public sector organizations. By using Structural Equation Modeling Partial Least Square (SEM-PLS), data from 189 public sector respondents were analyzed. The research tool was verified using tests for convergent validity, construct validity, and discriminant validity. The results indicate that organizational culture impacts job performance, OCB, and job motivation positively and significantly. Job motivation also has a positive and significant influence on OCB but is not significant in relation to job performance. Additionally, OCB positively and significantly affects job performance. This research addresses a gap in the existing literature by presenting a fresh perspective on the relationship between these factors within the public sector. The results of this study expand upon previous investigations and offer valuable insights for professionals seeking to enhance organizational performance in the public sector, particularly in terms of effectively implementing organizational culture and motivation strategies.